Effect of music combined with swaddling on pain in full-term newborns: randomized clinical trial - Gleicia Martins de Melo; Maria Vera Lúcia Moreira Leitão Cardoso; Paulo César de Almeida; Elisa Conceição Rodrigues (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to evaluate the effect of music applied within ten and 15 minutes, combined with swaddling, on behavioral (facial action) and physiological (heart rate) responses to pain in full-term newborns, before and during venipuncture for blood sampling. Methods: a randomized, triple-blind, clinical trial with 52 rooming in infants randomly assigned to four groups of 13: Experimental 1 (music [ten minutes] plus swaddling), Experimental 2 (music [15 minutes] plus swaddling), Control 1 (no music [ten minutes] plus swaddling), and Control 2 (no music [15 minutes] plus swaddling). Pain was measured using the Neonatal Facial Coding System in the basal and procedural moments. Results: experimental 2 group showed high pain absence (p < 0.05); low heart rate mean (p < 0.0001) in the basal and procedural (antisepsis, puncture, blood squeezing/aspiration, compression) moments. Conclusions: neonates who listened to 15 minutes of music plus swaddling showed a greater absence of facial pain actions.